Digital Economy and Youth Unemployment in the EU - Kolinets, Lesya; Akimjak, Amantius; Homotiuk, Andrii; Alaqrabawi, Rowaida; Stan, Leo (Journal of Education Culture and Society, 2026)
Aim. The aim of this research is to examine how various dimensions of the digital economy - namely, internet access, ICT-specific education, and digital workforce development - interact with educational and macroeconomic factors to influence youth unemployment across the EU. The study seeks to identify whether digitalisation serves as a lever to reduce youth joblessness and how its effects vary across countries. Methods. This study employs an Ordinary Least Squares (OLS) regression based on country-year panel data for 27 EU countries over the period 2013–2023, in conjunction with K-means cluster analysis. The quantitative model integrates seven variables, including household internet access, ICT education, GDP growth rate, to estimate their influence on youth unemployment. Cluster analysis is used to group countries based on shared characteristics in digital readiness and employment outcomes. Results. The regression results confirm that higher internet access and ICT education levels significantly reduce youth unemployment, while GDP growth plays a reinforcing role. General tertiary education showed a weak positive association with unemployment, suggesting potential skill mismatches. The cluster analysis revealed four distinct groups of countries, each with different digital profiles and policy needs. Conclusions. The study concludes that digital infrastructure, ICT skills, and economic growth are important for reducing youth unemployment. However, digitalisation should be combined with labour market and education policies adapted to different country groups. Practical Application. The results may support policymakers in designing coordinated strategies that link digital education, infrastructure, and macroeconomic reform to tackle youth unemployment.